Identifying novel genes that cause congenital heart disease - Wilsdon, Anna (2021)
Complex genetic networks underlie the development of the heart. Variants in some of these genes can lead to congenital heart disease (CHD). Despite the hundreds of genes that have been identified as causing CHD in humans, they only account for a small proportion of individuals with CHD. We carried out whole exome sequencing in the largest cohort of individuals with CHD reported at the time of publication, and identified three novel genome wide significant syndromic CHD genes; CDK13, PRKD1 and CHD4.